The Pedigree of 19th Century American Natural Literature: Origin and Development (Universitas Negeri Semarang, 2019)
To study the characteristics and significance of American natural literature in the 19th century, the American natural literature writers in 19th century can be analysed consistently. In the following three fields: prose, poetry and novels, several representative writers were selected. Their natural literary creation tendencies and the representative works of natural literature were compared in detail, and the features and meanings of 19th century American natural literature were analysed. The results showed that the American natural literature in the 19th century can promote the progress of American literature, and at the same time, it can enlighten the American people’s way of getting along with nature in the 19th century. By comparing with Chinese natural literature, it was also concluded that the ecological problem was a universal global problem. Its solution can’t be separated from the support of people all over the world. Natural literary writers also hoped that humans can share the earth’s ecosystem with nature in a friendly and harmonious manner.